Identificação do sexo do ornamental amazônico astronotus ocellatus (agassiz, 1831), por meio de videoceloscopia e biopsia gonadal - Mansur, Victor Ferreira Ribeiro (2018)
The objective was to evaluate the safety of videocloscopy and gonadal biopsy and to validate the methods of sexuality in A. ocellatus. A total of 31 adult animals (168.26 ± 54.09 g and 20.21 ± 2.48 cm) were used. For induction and anesthetic maintenance, use clove oil (140 mg / L and 70 mg / L water) in a recirculation system. In the pre-hereditary, antibiotic therapy with florfenicol (50 mg / kg) and analgesia with morphine (5 mg / kg), both intramuscularly, were performed. For access to the coelomatous cavity, the animal was kept in the supine position and an incision was made in the ventral midline. Then, the endoscope optic is inserted to visualize the gonads and identify the sex. Subsequently, with the aid of a laparoscopic forceps, a gonadal tissue fragment was collected and packed in 10% formal buffer. For synthesis of the cavity, the polyamide was used in a continuous simple pattern, and the animals were then monitored for anesthetic recovery. After 15 days of surgery, a healing was assessed and the stitches removed. Anesthesia anesthetic was used in the attempt of recovery and recovery of anesthetics for males and females. The surgical procedures, the presence of surgical parameters, healing, survival rate, food consumption and behavioral parameters were the following parameters. For validation of sexing methods, a histological analysis of the gonads was used as the gold standard method. The total time of videocloscopy, gonadal and gonadal and bipolar biopsies were significantly higher (p <0.05) for animals corrected as males (118.84 ± 108.04 s, 231.62 ± 226.59 if 720.00 ± (26.88 ± 38.08 s, 84.72 ± 36.63 s 366.66 ± 112.51 s). In only one animal was observed the gastrointestinal tract, dehiscence (p <0.05) for the period of 24h (61.45 ± 5.41%) and 36h ( 61.13 ± 6.13%) post-surgical compared to the control (preoperative) (83.87 ± 4.42%). In relation to height, differences (P <0.05) were observed for (1.45 ± 0.09) and 72h (3.12 ± 0.14) after surgery, when compared to control (2.48 ± 0.15). , 05) for trading behavior at 24h (1.61 ± 0.11), 36h (1.74 ± 0.14) and 60 h (1.61 ± 0.13) in one surgery, he attended the control group (2.54 ± 0.15). The children were submitted to a hypersensitivity test (p <0.05) at 12h (1.61 ± 0.08) and 24h (1.61 ± 0.09). 0.06). Total videoectomy accuracy was 96.7%. For wild and male animals, a specificity was 100% and 94.7%. On the other hand, the resistance was 94.7% and 100% respectively. A gonadal biopsy appeared to be 83%. In order to perform the anesthetic protocol and the surgical techniques of sonographic and safe gonadal videography and gonadal biopsy. In addition, the techniques were validated as sexing methods in A. ocellatus.